Peran Konsulat Amerika Serikat dalam Menjalin Hubungan Diplomasi dengan Pemerintah Kota Medan - Afrida Afrida; Halking Halking (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2016)
This study aims to determine the role of the United States Consulate in establishing diplomatic relations between the United States and the Government of Medan in the field of education. The method used in this study is the oral life history method (the method of oral history of life) and descriptive study. Analysis of the data in this study conducted using qualitative analysis that describes the phenomena associated with the role of the US consul in establishing diplomatic relations between the United States and the government of Medan. From data collection and processing is done, it has obtained the following results: the implementation of diplomatic relations between the United States and the Government of Medan in the field of education in 2007-2008 has been going well. And in the implementation Consul of the United States has run the tasks and role as well and not an obstacle. And until now Medan City government has always supported programs that created the American Consulate Consul performance and help the United States to take care of foreign affairs of the United States in the city of Medan. Diplomatic relations could be enhanced if the United States Consul exist socialize with Medan City government.